Potensi Senyawa Antibakteri Hasil Fermentasi Bakteri Endofit Dari Umbi Talas (Colocasia esculenta L.) - Aji Wahyu Wahiddatul Djakiah; Ayu Rachmawati; Desi Purwaningsih; Destik Wulandari (Journal Prima Health Science, 2019)
Endophytic bacteria are symbiotic microorganisms that live in plant tissues and an alternative producer of bioactive compounds that have the potential to be antibacterial. The study aims to determine the antibacterial activity of the bacteria Pseudomonas knackmussii and Bacillus siamensis in inhibiting the growth of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 as well as knowing the optimum time of fermentation of endophytic bacteria with the greatest antibacterial activity. The study was conducted in several stages, namely the identification of pathogenic bacteria and endophytic bacteria, fermentation of endophytic bacteria and antibacterial activity tests. Some treatment groups were ciprofloxacin 5μg as a positive control, sterile paper with sterile Brain-Heart Infusion (BHI) media as negative control andendophytic bacterial fermentation supernatant for 4 days as a test group. The results showed endophytic bacteria from taro tubers had antibacterial activity against S. aureus ATCC 25923 and E. coli ATCC 25922. The optimum time of fermentation with the largest antibacterial activity against S. aureus was on the 3rd day with inhibitory value of 9.69 mm produced by P. knakcmussii and 9,20 mm by B. siamensis while for E. coli the optimum time to ferment P. knackmussii is on the 2nd day with inhibitory values of 11.83 mm and B. siamensis on the 4th day of 10.78 mm.